2020
DOI: 10.21203/rs.2.19232/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social marketing interventions to promote physical activity among 60 years and older: a systematic review of the literature

Abstract: Background: Falls are a significant source of morbidity in people aged 65 and over, affecting one in three people in this age group. The scientific evidence indicates that physical activity is the most effective method for preventing falls among seniors. Although public health professionals often use social marketing to design and plan successful interventions, its use to promote physical activity and prevent falls among older people remains low. This article aims to provide a new systematic literature review … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, it is difficult to evaluate the efficiency of Social Marketing in promoting PA among seniors. Few strategies used so far did not apply all the seven benchmark criteria ( 49 ). Fujihira et al ( 41 ) and Goethals et al ( 49 ) have showed that as a program frequently uses the social marketing benchmark criteria defined by Andreasen, it becomes more and more effective at changing the behaviors of its target population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is difficult to evaluate the efficiency of Social Marketing in promoting PA among seniors. Few strategies used so far did not apply all the seven benchmark criteria ( 49 ). Fujihira et al ( 41 ) and Goethals et al ( 49 ) have showed that as a program frequently uses the social marketing benchmark criteria defined by Andreasen, it becomes more and more effective at changing the behaviors of its target population.…”
Section: Discussionmentioning
confidence: 99%
“…Few strategies used so far did not apply all the seven benchmark criteria ( 49 ). Fujihira et al ( 41 ) and Goethals et al ( 49 ) have showed that as a program frequently uses the social marketing benchmark criteria defined by Andreasen, it becomes more and more effective at changing the behaviors of its target population. Other reviews ( 18 , 19 , 50 ) have used the same classification criteria as Andreasen and reported similar findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interviewees were sports trainers and older adults who were participating in the Social MArketing and Physical activity in Elderly (SMAPE) study [13]. The main objective of the SMAPE study was to determine whether a social marketing program based on the promotion of group balance workshops for people aged 60 years and over increases their attendance rate in sessions of "activities adapted physical skills."…”
Section: Overviewmentioning
confidence: 99%
“…It was highlighted that the original article [ 1 ] contained an error in Table 3 . Also, two previous studies (Kamada et al 2013, Kamada et al 2015) were mentioned in the Discussion section but were missing from the reference list.…”
mentioning
confidence: 99%